1975
DOI: 10.1207/s15327752jpa3905_9
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Creativity by the Stroop Color and Word Test

Abstract: The development of a valid and reliable measure of creativity has been a challenging problem to psychologists. Gamble and Kellner (1968) have suggested that the Stroop Color and Word Test (SCWT) might be such a measure. The advantages of the Stroop include that it tests basic processes, is stable over long periods of time, and is easy to administer and score. The present study investigated the relationship of the Stroop to three independent measures of creativity: a verbal task, a nonverbal task, and ratings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
4

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 15 publications
1
39
1
4
Order By: Relevance
“…The clinical version Stroop ColourWord Task has been used in myriad studies on a wide range of topics (cf, Goshiki & Miyahara, 2008;MacLeod, 1996;MacLeod & MacDonald, 2000). Adequate psychometric properties have been reported for this measure (Golden, 1975(Golden, , 1978Schretlen, 1996).…”
Section: Central Executivementioning
confidence: 99%
“…The clinical version Stroop ColourWord Task has been used in myriad studies on a wide range of topics (cf, Goshiki & Miyahara, 2008;MacLeod, 1996;MacLeod & MacDonald, 2000). Adequate psychometric properties have been reported for this measure (Golden, 1975(Golden, , 1978Schretlen, 1996).…”
Section: Central Executivementioning
confidence: 99%
“…In relation to the cognitive functioning of creative individuals, Stavridou and Furnham (1996) and Green and Williams (1999), found that individuals with high divergent thinking ability had intact inhibition skills. Further, Gamble and Kellner (1968) and Golden (1975) found that creative individuals were less susceptible to interference than non-creative individuals, as measured by the Stroop task. On the other hand, Carson, Peterson and Higgins (2003) found that highly creative individuals had lower scores on a measure of latent inhibition, the ability to filter out both internal and external stimuli previously experienced as irrelevant.…”
mentioning
confidence: 98%
“…Overall, in this test, four words (green, yellow, blue, and red) are presented for 96 times; in 50% of the cases, the presented words are congruent and in 50% of the cases the presented words are incongruent. Each stimulus is presented on the screen for 2 s, and the time interval between presentations of the stimuli is 0.800 s. Golden (1975) reported Cronbach's alpha values of 0.85, 0.82, and 0.73 for the single versions of the test. In addition, test-retest reliability estimates of 0.80 to 0.91 have been reported for the test [20].…”
Section: Simple Stroop Testmentioning
confidence: 99%
“…Each stimulus is presented on the screen for 2 s, and the time interval between presentations of the stimuli is 0.800 s. Golden (1975) reported Cronbach's alpha values of 0.85, 0.82, and 0.73 for the single versions of the test. In addition, test-retest reliability estimates of 0.80 to 0.91 have been reported for the test [20].…”
Section: Simple Stroop Testmentioning
confidence: 99%